Hierarchy of Needs of the Main Character in Habiburrahman El Shirazy's Ayat-Ayat Cinta: A Study of Abraham Maslow's Psychology - Wulan Suci Novianti; Rohanda Rohanda; Isma Fauziah; Palendika Alandira (Hasanuddin University, 2025)
This research discusses the psychological needs of the main character in the novel Ayat-Ayat Cinta by Habiburrahman El Shirazy using Abraham Maslow's Hierarchy of Needs theory. The main focus of the research lies on five levels of needs: physiological, security, love and belonging, appreciation, and self-actualization. Through descriptive qualitative method and humanistic psychology approach, this research explores how Fahri’s character articulates and meets his needs. The results show that Fahri successfully fulfills each stage of need step-by-step, starting with basic necessities and culminating in self-actualization, evident in his intellectual, spiritual, and moral development. The findings reveal that Fahri's character is a representation of an individual who has successfully reached the stage of self-actualization, and is able to contribute to his social environment through knowledge and faith.